Taxonomic confusion among gall-thrips and host-plants, with three newcombinations from the genus Austrothrips (Thysanoptera, Phlaeothripidae) - Mound, Laurence (Zootaxa, 2020)
The genus Austrothrips is considered a nomen dubium because the types are lost and the type species description is uninformative. Austrothrips flavitibia Moulton is transferred to the genus Teuchothrips and Austrothrips vanuaensis Moulton is transferred to the genus Solomonthrips. The gall-inducing Austrothrips cochinchinensis Karny is transferred to Ocnothrips as a senior synonym of the type species, O. indicus. The host of cochinchinensis is recognised as a vine-like shrub, Getonia floribunda, that is widespread between western India and southeast China.